Pulmonary Hypertension Due to Left Heart Disease: Diagnosis, Pathophysiology, and Therapy. Issue 6 (June 2020) - Al-Omary, Mohammed S.; Sugito, Stuart; Boyle, Andrew J.; Sverdlov, Aaron L.; Collins, Nicholas J.
Abstract : Pulmonary hypertension (PH) due to left heart disease (LHD) is the most common type of PH and is defined as mean pulmonary artery systolic pressure of >20 mm Hg and pulmonary capillary wedge pressure >15 mm Hg during right heart catheterization. LHD may lead to elevated left atrial pressure alone, which in the absence of intrinsic pulmonary vascular disease will result in PH without changes in pulmonary vascular resistance. Persistent elevation in left atrial pressure may, however, also be associated with subsequent pulmonary vascular remodeling, vasoconstriction, and an increase in pulmonary vascular resistance. Hence, there are 2 subgroups of PH due to LHD, isolated postcapillary PH and combined post- and precapillary PH, with these groups have differing clinical implications. Differentiation of pulmonary arterial hypertension and PH due to LHD is critical to guide management planning; however, this may be challenging. Older patients, patients with metabolic syndrome, and patients with imaging and clinical features consistent with left ventricular dysfunction are suggestive of LHD etiology rather than pulmonary arterial hypertension. Hemodynamic measures such as diastolic pressure gradient, transpulmonary gradient, and pulmonary vascular resistance may assist to differentiate pre- from postcapillary PH and offer prognostic insights. However, these are influenced by fluid status and heart failure treatment. Pulmonary arterial hypertension therapies have been trialed in the treatment with concerning results reflecting disease heterogeneity, variation in inclusion criteria, and mixed end point criteria. The aim of this review is to provide an updated definition, discuss possible pathophysiology, clinical aspects, and the available treatment options for PH due to LHD.